Assessment of Coronary Artery Bypass Graft (CABG) Patency and Graft Disease Using Multidetector Computed Tomography (MDCT) - Song, Bong Gun; Yang, Hyun Suk; Doh, Joon Hyung; Jang, Hong; Kang, Gu Hyun; Park, Yong Hwan; Chun, Woo Jung; Oh, Ju Hyeon; Ko, Sung Min; Hwang, Hweung Kon (IntechOpen, 2011)
None